EFEKTIFITAS MEDIA KOTAKMATIKA DALAM MENINGKATKAN KEMAMPUAN PERKALIAN PADA ANAK BERKESULITAN BELAJAR - Nining Purwasih (Universitas Negeri Padang, 2015)
The Background of this research is found a child who has difficulties in learning in 4th class of Elementary school. This child can’t to break the exercise of the arithmetic operations of multiplication and also can’t solve the multiplication of units and tens. In order to increasing ability of arithmetic multiplication operation by using kotakmatika media in mathematics lesson. This research using Single Subject Research method with A-B-A design. The datas about ability of multiplication of the children is written. Technical analysis of the data used Visual Analysis of Graphs. Results were analyzed include the number of observations in the baseline condition (A-1) 5 times, intervention (B) 8 times, baseline (A-2) 4 times. The results showed that kotakmatika media can enhance child’s ability significantly. It can be seen from the analysis that the trend began to increased. At baseline conditions (A-1) children are only able to answer the multiplication 6 to 10 of 20 about 30% correctly . After being given the treatment by the media of kotakmatika, child can answer questions about the multiplication correctly abouts 80% of the 20 questions that exist. Besides the intervention is stopped, then returned to kebaseline (A-2) in this condition the child is able to answer questions about the multiplication of 80% of the 20 questions which exist. This shows that the media kotakmatika can improve arithmetic operations of multiplication 6 to 10 in child learning disabilities. Based on data analysis that has been done, it can be concluded that through media kotakmatika can improve learning difficulties in child multiplication at fourth class. Therefore, it is suggested that in arith matic of the teacher to use kotakmatika media can improve multiplication ability in child ability.